Redesign Shovel To Be More Efficient, Convenient and Safe - Azmee, Muhammad Iqbal Al Hakim bin; Mulkan, Alyssa Mulyani binti Mohd; Halimoon, Hasrul bin; Adnan, Alwani binti (Universitas Negeri Padang, 2021)
Shovel, hoe, fork hoe, and hole digger are commonly used in various material handling work manually. So far, only a few studies have been done for special ergonomically designed tool that will serve the purposes of the shovel, hoe, fork hoe, and hole digger. This research examined the efficiency of specifically combined tools shovel, hoe, fork hoe, and hole digger named as multifunction shovel for digging, lifting, and moving bulk materials such as soil, coal, gravel and sand. This project was built to minimize physical workload, reduce the time taken to perform this task, and mitigate health and safety risks. There were 20 respondents involved in this study and they were required to test the project before completing observation checklists and questionnaires. The findings revealed that the students had strong approval on each function and feature of the project. There were a few recommendations on how the project could be improved to be safer and more efficient.